The 7SK/P-TEFb snRNP controls ultraviolet radiation-induced transcriptional reprogramming - Studniarek, C; Tellier, M; Martin, PGP; Murphy, S; Kiss, T; Egloff, S (Cell Press, 2021)
Conversion of promoter-proximally paused RNA polymerase II (RNAPII) into elongating polymerase by the positive transcription elongation factor b (P-TEFb) is a central regulatory step of mRNA synthesis. The activity of P-TEFb is controlled mainly by the 7SK small nuclear ribonucleoprotein (snRNP), which sequesters active P-TEFb into inactive 7SK/P-TEFb snRNP. Here we demonstrate that under normal culture conditions, the lack of 7SK snRNP has only minor impacts on global RNAPII transcription without detectable consequences on cell proliferation. However, upon ultraviolet (UV)-light-induced DNA damage, cells lacking 7SK have a defective transcriptional response and reduced viability. Both UV-induced release of "lesion-scanning" polymerases and activation of key early-responsive genes are compromised in the absence of 7SK. Proper induction of 7SK-dependent UV-responsive genes requires P-TEFb activity directly mobilized from the nucleoplasmic 7SK/P-TEFb snRNP. Our data demonstrate that the primary function of the 7SK/P-TEFb snRNP is to orchestrate the proper transcriptional response to stress.